ChemInform Abstract: Copper‐Free Postsynthetic Labeling of Nucleic Acids by Means of Bioorthogonal Reactions. Issue 37 (September 2015) - Merkel, Marcus; Peewasan, Krisana; Arndt, Stefanie; Ploschik, Damian; Wagenknecht, Hans‐Achim
Abstract Review: [114 refs.